Language and communication abilities in temporal lobe epilepsy patients: right vs. left hemisphere's processing - Lomlomdjian, A. C. (2019)
Purpose : Most of previous studies in temporal lobe epilepsy have focused on production and comprehension of single word and sentence level analysis, centered in the left hemisphere. Although communication abilities, in which right hemisphere ' s processing is required, have remained unexplored in this population. The purpose of this study was to investigate interictal communication abilities in patients with right lateralized medial temporal lobe epilepsy (RTLE) comparing it with that of patients with left TLE (LTLE) to determine potential impairments and it lateralizing value. Methods : 120 pharmacoresistant TLE patients were evaluated: 55 with RTLE and 65 with LTLE. Subjects underwent a battery of language tests that measure: naming, verbal fluency, verbal inhibition, logic- temporal sequencing, conversational discourse, prosody, comprehension, narrative discourse, indirect speech acts and idiom expressions. Results were compared to those of normal population and deficit was established when performance was below the Z - 1.5 or percentile 5. Statistical significant value was considered at p < 0.001. Results : RTLE compared to LTLE patients, showed significant poorer performance in conversational and narrative discourse, idiom expressions’ and indirect speech ' s comprehension and emotional prosody. RTLE group had a tendency to tangential and disintegrated speech, lack of hierarchical and categorized codification and a significant deficit in social meaning inference. Otherwise, LTLE group showed lower performance in logical temporal sequencing No statistical differences were found in single word level tests analysis. Conclusion : RTLE patients showed communication deficits which are similar to been described in right hemisphere damaged patients due to other etiologies. These communication deficits demonstrated to have a lateraling value and could guide cognitive stimulation programs. Right anterior and mesial temporal structures would have a direct role in prosody processing, and an important role in discourse and pragmatic processing as a link between semantic, language and social processing to build a coherent meaning according to the context.